Efeitos da interação entre fósforo e excesso de ferro nas características morfométricas e fisiológicas de cultivares de arroz (Oryza sativa L.) - Tavares, Miriam da Silva (2017)
Iron (Fe) is an important micronutrient for several physiological processes of plants. However, Fe toxicity is a problem that affects many areas of rice cultivated in lowland environments. The antagonistic interaction between Fe and phosphorus (P) is a subject of considerable interest in flooded environments. The responses of different cultivars to different levels of P utilization in conditions of excess Fe can provide new information for larger tolerance and efficiency in nutrient absorption. This work aimed to characterize the effects of phosphate nutrition on rice cultivars submitted to Fe toxicity, identifying possible mechanisms of tolerance. Before studying the interaction of P and Fe in the growth of rice in nutrient solution, three rice cultivars (Irga 425, Irga 424 and Br/Irga 409) were exposed at different concentrations of P (2,5, 15, 25 and 35mg L-1) and Fe (2, 100, 200 and 300mg L-1) in order to investigate the variation of the responses of the cultivars to the parameters of root and shoot growth, as well as the photosynthetic parameters. We found that the larger responses in the assimilation rate of CO2 and Rubisco carboxylation efficiency were observed at concentrations of 15 and 25 mg L-1 of P. The larger root morphometric damages, the lower assimilation rate of CO2, Rubisco carboxylation efficiency and the lower dry mass of roots and shoots were observed at the concentrations of 200 and 300mg L-1 of Fe. Were selected the concentrations of P (2,5, 15, 25mg L-1) and Fe (200mg L-1) to obtain root, nutritional, physiological and biochemical morphometric responses rice cultivars. In one experiment, the cultivars were exposed to excess Fe (200mg L-1) combined with the two concentrations of P (2,5, 25mg L-1) in nutrient solution, for 15 and 22 days. Fe excess altered the organization of the quiescent center, reflecting changes in the pattern of cell division. With the increase in P concentration under conditions of Fe excess, the cultivar Irga 425 presented higher root length, surface area and root volume, as well as higher of P concentration in the shoot tissue and absorption efficiency than the cultivars Br/Irga 409 and Irga 424. Except for the concentration of Fe and manganese in the tissues of the shoot, the increase in P concentration in the nutrient solution, under conditions of Fe excess, did not influence the absorption of copper and zinc. In another experiment, the cultivars were cultivated in pots having sand as substrate and twosand with distinct concentrations of Fe (2 e 200mg L-1) combined with two concentrations of P (2,5, 15mg L-1) in nutrient solution were tested, for 60 days. In general, all cultivars presented some degree of sensitivity to Fe excess, which caused impairment of the assimilation rate of CO2, stomatal conductance, reductions in chlorophyll concentrations, which reflected in reductions in growth. The cultivar Irga 425 presented greater capacity of use of the P, in conditions of Fe toxicity, through increments in the photosynthetic activity and activity of superoxide dismutase.